The Prague cemetery - Eco, Umberto (Houghton Mifflin Harcourt, 2011)
19th-century Europe, from Turin to Prague to Paris, abounds with the ghastly and the mysterious. Jesuits plot against Freemasons. In Italy, republicans strangle priests with their own intestines. In France, during the Paris Commune, people eat mice, plan bombings and rebellions in the streets, and celebrate Black Masses. Every nation has its own secret service and secret organizations that are plotting against each other, perpetrating conspiracies and even massacres. There are false beards, false lawyers, false wills, even false deaths. One of their most powerful tools is forgery. A well-made forged document can alter people's perceptions of a religion or group, rally the masses to war, or even change history. Of the best forgers of the era is Simonio Simonini, and his latest work of deception will help lay the groundwork for the most infamous forged work of all time: The Protocols of the Elders of Zion. From the Dreyfus Affair to the Protocols of the Elders of Zion, the Jews are blamed for everything. One man connects each of these threads into a massive crazy-quilt conspiracy within conspiracies. Here, he confesses all, thanks to the author's ingenious imagination, this book is a thrill ride through the underbelly of actual, world shattering events. -- Provided by publisher.